Should we stay together - Larson, Jeffry (San Francisco: Jossey Bass, 2000)
Contents: Myths about preparing for marriage. The marriage triangle: three factors that predict your future marital satisfaction. The marriage triangle, factor 1
Icludes bibliographical references
Keywords: Mate Selection